1986
DOI: 10.1159/000116042
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Presenting with Recurrent Acute Demyelinating Polyneuropathy

Abstract: We report a patient who in the course of 3 years developed 3 distinct episodes of an acute demyelinating neuropathy, each fulfilling the criteria set up by an ad hoc committee of the National Institute of Neurological and Communicative Disorders and Stroke for acute Guillain-Barre syndrome. Each episode was associated with strong serological evidence for lupus erythematosus. The episodes were separated by 1–2 years and each was followed by near complete clinical recovery. The only systemic feature was a pleura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The disorder may be recurrent. 86 In a general overview of the problems of SLE" it was pointed out that peripheral neuropathies occur in all types of connective tissue disease and that the neuropsychiatric manifestations of SLE were most similar to those of polyarteritis nodosa (see below). According to Johnson and K i c h a r d~o n ,~~ "SLE of the nervous system is, in most cases, a vascular disease involving very small vessels."…”
Section: Other Neuropathies Associated With Abnormal Blood Rheoloqymentioning
confidence: 99%
“…The disorder may be recurrent. 86 In a general overview of the problems of SLE" it was pointed out that peripheral neuropathies occur in all types of connective tissue disease and that the neuropsychiatric manifestations of SLE were most similar to those of polyarteritis nodosa (see below). According to Johnson and K i c h a r d~o n ,~~ "SLE of the nervous system is, in most cases, a vascular disease involving very small vessels."…”
Section: Other Neuropathies Associated With Abnormal Blood Rheoloqymentioning
confidence: 99%
“…Most of the SLE patients reported to date have AIDP. 3,[10][11][12] Rarely, AIDP may be the first manifestation of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported neurological manifestations similar to GBS in patients with SLE. [8][9][10][11][12][13][14] Some claimed a possible involvement of immunological abnormalities in SLE in the pathogenesis of GBS. Robson et al 14 reviewed these cases and suggested the mechanisms of GBS onset in SLE patients.…”
Section: Discussionmentioning
confidence: 99%